Alternative Learning Media for Environmental Health during the Covid-19 Pandemic - Brilyan Anindya Dayfi; Betty Sunaryanti; Nengah Kundera; Sulistyani Prabu Aji (YCMM, 2022)
In this study, we will discuss the critical period of transmission due to Covid-19 requiring teaching and learning activities to be carried out through Distance Online Learning. This phenomenon requires every lecturer in particular to be able to use an appropriate online learning media platform so that the learning process runs smoothly as desired. Researchers use one of the online learning media that can be applied by lecturers, namely by using Google Classroom media. The Google Classroom learning media can be used easily by lecturers in the online teaching and learning process, because it is relatively easy to use. The final result of this research is to describe the use of Google Classroom as an online-based learning media. The research method used is literature study, observation, and interviews with course lecturers at Sari Mulia University. The results of the study were based on interviews with the lecturers. Google Classroom is easy to use for Sari Mulia University lecturers. The features found in Google Classroom are quite easy to learn and apply by lecturers. The results of the study were determined based on a literature review, namely Google Classroom, which made it easier for lecturers to manage time in managing classes and improve communication with students.